Impact of risks in innovative management of the green economy and ways to reduce IT - Rashidov, Jamshid (MMIT Proceedings, 2025)
The article identifies various risks in innovative green economy management and examines their impact. Proposals and recommendations have also been developed for measures to prevent and eliminate these risks.